2020
DOI: 10.1186/s12967-020-02300-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies for smoke inhalation injury: a review

Abstract: Background: Smoke inhalation injury increases overall burn mortality by up to 20 times. Current therapy remains supportive with a failure to identify an optimal or targeted treatment protocol for smoke inhalation injury. The goal of this review is to describe emerging therapies that are being developed to treat the pulmonary pathology induced by smoke inhalation injury with or without concurrent burn injury. Main body: A comprehensive literature search was performed using PubMed (1995-present) for therapies no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Specific treatments have been tested to prevent IMV, complications, and poor outcomes. Some studies observed that N acetylcysteine and inhaled anticoagulants (such as heparin) may effectively treat inhalation injury, significantly improving lung compliance and airway obstruction, reducing reintubation rates, increasing the number of ventilator-free days, and decreasing hospital length of stay, and mortality [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Specific treatments have been tested to prevent IMV, complications, and poor outcomes. Some studies observed that N acetylcysteine and inhaled anticoagulants (such as heparin) may effectively treat inhalation injury, significantly improving lung compliance and airway obstruction, reducing reintubation rates, increasing the number of ventilator-free days, and decreasing hospital length of stay, and mortality [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…MODS, ARDS and shock are still considered the main causes of death in burns patients ( 29 ). Patients mortalities within 48 h after SII predominantly result from obstruction and asphyxia ( 1 ). Septic shock caused by exacerbated inflammatory reaction, rapid and extensive fluid transfer in burn and non-burn tissues leading to progressive hypovolemic shock forms an important cause of burn shock-related mortality ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smoke inhalation injury (SII) is the most common cause of mortality in patients with fire burn injuries ( 1 ). Most hospitalized patients with burns usually have accompanying inhalation injury, and the incidence rate of SII is positively correlated with mortality rates ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of antioxidants in burns has a protective effect in oxidative tissue damage and organ failure [12]. The effect of hyperbaric oxygenation (HBO) in patients with burns provides an improvement in the gas exchange of body tissues with subsequent activation of metabolic processes and a decrease in the intensity of inflammatory reactions [4,6]. In addition, due to tissue hyperoxygenation, HBO contributes to maintaining the activity of antioxidant protection at a sufficient level [7][8][9]13].…”
Section: Introductionmentioning
confidence: 99%